ANALISIS PROSES KREATIF PENULISAN SKENARIO “JALAN PERKAWINAN” KARYA ARTHUR S. NALAN - Akhmad, Imam; Jatnika, Anggit Surya (Institut Seni Budaya Indonesia Bandung, 2023)
Abstract The creative process of a work is something that needs to be studied in order to produce a comprehensive understanding of the creation of a work. With in-depth study, the creative process can be used as a lesson and carried out by other people who are interested in the creative process of a work. The work examined in this research is the screenplay for the film